2007
DOI: 10.1029/2007gl030523
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of the lower‐mantle ferropericlase across the electronic spin transition

Abstract: [1] Electrical conductivity of the lower-mantle ferropericlase-(Mg 0.75 ,Fe 0.25 )O has been studied using designer diamond anvils to pressures over one megabar and temperatures up to 500 K. The electrical conductivity of (Mg 0.75 ,Fe 0.25 )O gradually rises by an order of magnitude up to 50 GPa but decreases by a factor of approximately three between 50 to 70 GPa. This decrease in the electrical conductivity is attributed to the isosymmetric high-spin to low-spin transition of iron in ferropericlase. That is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…3b). Such behaviour strongly suggests that the conductivity drop in samples dominated by Fe 2þ is due to the HS to IS transition in Fe 2þ , where electron mobility is reduced due to the spin transition, analogous to the behaviour of (Mg,Fe)O [23][24][25] . The greater drop at high temperature (brown circles in Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…3b). Such behaviour strongly suggests that the conductivity drop in samples dominated by Fe 2þ is due to the HS to IS transition in Fe 2þ , where electron mobility is reduced due to the spin transition, analogous to the behaviour of (Mg,Fe)O [23][24][25] . The greater drop at high temperature (brown circles in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Laboratory electrical conductivity data of the relevant minerals are an important component of the approach, because they provide critical data on how the chemical and thermal state of the material influences the conductivity. Laboratory measurements of single-phase Mg 0.9 Fe 0.1 SiO 3 perovskite 10,11 and a pyrolite mantle assemblage 12 (Fe 3þ /SFe of the perovskite phase estimated to be 12% and 30%, respectively) 22 show a decrease in conductivity 450 GPa, comparable to the electrical conductivity decrease caused by HS-LS spin cross-over of Fe 2þ in (Mg,Fe)O (refs [23][24][25]. The drop in silicate perovskite conductivity has been attributed to a HS-LS transition of Fe 3þ (refs 10-12); however, this explanation is ruled out by the results in the present work.…”
Section: Resultsmentioning
confidence: 96%
“…If the former is the case, then the electrical conductivity of mantle PPv should be very low and may not be important for the electromagnetic coupling. Furthermore, even with the Fe enrichment, the electrical conductivity of Fp remains quite low at high P and the Fe spin transition at midmantle P further decreases the conductivity (31).…”
Section: Resultsmentioning
confidence: 97%
“…Recently it has been shown that Fe in mantle silicates and oxides undergoes a HS → LS transition (7-9) which influences important physical properties such as density (30), optical properties (11), and electrical conductivity (31). It appears that spin pairing monotonically increases with P in Fp with mantle-related compositions where no significant structural transition exists in the mantle.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] But in a long time, the accurate conductivity measurements were ever hard to be taken on diamond anvil cell (DAC) due to the difficulties from sample configuration and the rigorous geometrical limitations coming from small sample and electrodes. [5][6][7][8][9][10][11][12] For solving the problem, the techniques of thin film electrodes integration and electric field analysis (EFA) were combined together in conductivity measurement by four-probe method (FPM) in DAC and the accuracy has been achieved. [13][14][15][16] These studies indicated that only if the size and the thickness of sample chamber and the geometry configuration of electrodes were carefully designed, could the conductivity be obtained by FPM configuration and EFA methods.…”
mentioning
confidence: 99%